Access to Government Micro-data for SME Internationalization Research - Niroui, Fariba (University of Waterloo, 2012)
International entrepreneurship (IE) is “a combination of innovative, proactive and risk-seeking behaviour that crosses national borders and is intended to create value in organizations”. The IE literature has been concerned with entrepreneurial behaviour in multiple countries and cross-border studies of entrepreneurship and international activities of small and medium-sized enterprises (SME). Due to the potential for SMEs to serve as significant sources of export, considerable research has been conducted regarding their internationalization. However, despite attempts to integrate concrete frameworks of international entrepreneurship, some primary issues have not been adequately addressed and IE researchers are faced with challenges including insufficient micro-data for advancing quality research. The main objective of this thesis is to study and explore the limitations on researchers to access governmental data regarding small firms operating internationally and use it for scientific purposes. Despite company data being compiled and publicly available in some countries, such as Germany, other countries, including Canada, have not made any such efforts in a coherent way. There is a significant disconnect in the Canadian context between internationalization and firms’ data. This shortcoming may stem from various sources, including the legal framework in Canada for accessing data and a lack of sufficient financial support and expertise to gather and integrate such data. Furthermore, the type of data available to the research community through statistical institutions were identified and analyzed, as were access methods. With the increasing interest of researchers in accessing data gathered by the government, the formation of anonymized records or anonymized micro-datasets has acquired great importance. Therefore, the primary approach is to explore the extent to which data regarding firms’ characteristics and internationalization activities are currently available to the research community, as well as to ensure the confidentiality of official statistics, most notably in the Canadian context. The research resulted in the confirmation of data availability in Canada through government and statistical organizations. The latter bodies can provide researchers and research organizations access to some data but limitations arise in providing micro-datasets to researchers due to confidentiality issues; these constraints were identified and further analyzed. Moreover, this research has studied methods to overcome these limitations and assess the shortcomings in micro-data in order to advance quality research. Methods and recommendations were introduced and studied to allow researchers access to essential data and information while maintaining confidentiality.
Keywords: International Entrepreneurship; Small and Medium-sized Enterprises; Internationalization; Government Micro-data; Business Micro-data; Micro-data Confidentiality; Confidentiality Protection; Management Sciences